Respuesta :
If (1,1) is translated to (1,4) the graph is shifted upwards by 3 units. So a constant of 3 is added to the parent function.
f(x)=x^3 now add 3 to f(x)
g(x)=x^3+3
f(x)=x^3 now add 3 to f(x)
g(x)=x^3+3
Answer:
[tex]y=x^3+3[/tex]
Step-by-step explanation:
The graph of y = x 3 is translated so that the point (1, 1) is moved to (1, 4).
the point (1, 1) is moved to (1, 4), 1+3=4
So 3 is added with y to get (1,4)
To get the equation of new graph , add 3 with y
[tex]y=x^3[/tex]
To add 3 with y, we put +3 at the end of the given equation
the new equation becomes
[tex]y=x^3+3[/tex]